Comparing particle transport in JET and DIII-D plasmas: gyrokinetic and gyrofluid modelling. (26th November 2020) - Fransson, E.; Eriksson, F.; Oberparleiter, M.; Held, M.; Mordijck, S.; Nordman, H.; Salmi, A.; Strand, P.; Tala, T.
Abstract: Transport modelling, for two dimensionless collisionality scaling experiments at the Joint European Torus (JET) and DIII-D with three discharges each, is presented. Experimental data from JET (Tala et al 2019 Nucl. Fusion 59 126030) and DIII-D (Mordijck et al 2020 Nucl. Fusion 60 066019) show a dissimilar dependence in the density peaking from the source and turbulent transport. The discharges from the JET collisionality scan show that the source is dominant for the density peaking, which is contrary to DIII-D where the transport is the main cause for the peaking. In this article, the different dependency on the source is studied by investigating the zero flux density gradient (peaking factor) at radial position ρ t  = 0.6 and by calculating the averaged perturbed diffusion and pinch between ρ t  = 0.5 and ρ t  = 0.8. Results show that the difference of the normalized temperature gradients have the largest and considerable impact on the peaking factor. The calculated diffusion and pinch showed good match with the experimental measured perturbed values. The calculated ratio of the particle balance pinch and diffusion explained the difference in peaking from turbulent transport, a high ratio for DIII-D yielding high peaking and a low ratio for JET yielding low peaking. However the particle balance diffusion, which suppresses the peaking from the source, was high for DIII-D and low for JET. Thusly, explaining the particle source much larger impact on the peaking at JET.